ANALISIS RASIO LIKUIDITAS, LEVERAGE DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. BANK CENTRAL ASIA, TBK. CABANG MANADO - Pangemanan, Ireine Wulan; Karamoy, Herman; Kalalo, Meily (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
In assessing the financial performance of the company, one of the indicator used is accounting information in the form of companyâ€™s financial statements. This research was conducted at PT. Bank Central Asia, Tbk Manado Branch with the purpose to analyze the financial statements in assessing the financial performance of companies, especially banking companies. The method of analysis used in this research is analytical descriptive method. From the existing financial statements performed financial ratio analysis to be able to describe the company's financial performance. The result of the liquidity ratio consisting of QR and LDR as a whole shows the company's ability to pay its short-term and long-term liability is very good, and it is ranked at the bank's 1st level of health. The results of solvency ratios assessed on the basis of DAR is unable to describe the company's financial performance because funding is entirely derived from liabilities without any capital value. The results of profitability ratios consisting of NPM, ROA, and BOPO show that the company's ability to earn profit through all available sources shows an excellent level of efficiency, and it is ranked at the bank's 1st level of health..Â Keywords: Financial Performance Assessment, Financial Ratios